The energy balance of maize production – alternative approaches - Horváth, Tibor; Nyéki, Anikó; Neményi, Miklós (Acta Agraria Debreceniensis, 2018)
Agricultural production is a crucial area, perhaps the most important for humanity. This is the only area which cannot be avoided. Therefore, it is of utmost importance to know how sustainable the system is in the long run as regards energy consumption. We have chosen the maize production sector as the main focus of this study. This crop is especially important all over the world, therefore; it requires significant input also in terms of energy. Currently, the system of maize production (as with the others) operates as an open energy system.This study aims to examine how much of the agricultural land’s energy demand could be met with the help of the byproducts of 1 hectare of agricultural land - operating as a closed system, using only the remaining maize stalk and cob byproducts for energy - under the conditions of Hungarian maize production.Energy demand is largely determined by the land’s fertilizer requirement, followed by the input factor of the energy demand of the machinery during earthwork and transport.The study assumes that the energy from the byproducts of maize production will be used exclusively with biogas technology. This can even be implemented on a county level. The final question is whether the maize production system will be able to sustain itself solely by using its own byproducts.